(untitled) (Journal of Recent Advances in Applied Sciences (pISSN 0970-1990), 2026)
Introduction: Fibroepithelial lesions of the breast comprise a diverse group of biphasic tumors ranging from benign fibroadenomas to phyllodes tumors, which are further categorized as benign, borderline, and malignant. Although fibroadenomas are common benign breast lesions, phyllodes tumors are relatively rare and may clinically and radiologically mimic fibroadenomas, making accurate diagnosis challenging. The coexistence of multiple fibroepithelial tumor types in a single patient is exceptionally uncommon and highlights the complexity of these lesions. Aim & Objective: To present a rare case demonstrating the complete histopathological spectrum of fibroepithelial breast lesions in a single patient and to emphasize the importance of careful pathological evaluation for appropriate diagnosis and management. Material & Methods: A 46-year-old female presented with bilateral breast lumps clinically suggestive of benign breast lesions. Radiological evaluation favored fibroadenomas. Surgical excision of the breast masses was performed, followed by detailed histopathological examination of all excised specimens. Results: Histopathological analysis revealed three distinct fibroepithelial lesions within the same patient, including fibroadenoma, benign phyllodes tumor, and malignant phyllodes tumor. The lesions showed overlapping radiological appearances, contributing to diagnostic difficulty. Microscopic evaluation demonstrated varying stromal cellularity, atypia, mitotic activity, and tumor margins corresponding to the different pathological entities. The presence of a malignant phyllodes tumor necessitated close clinical follow-up and further oncological management. Conclusion: This rare case illustrates the broad histopathological spectrum of fibroepithelial breast lesions and highlights the limitations of radiological diagnosis alone. Comprehensive histopathological assessment remains essential for accurate classification, prognostication, and treatment planning. Early recognition of